Mode Analysis of Horizontal Axis Wind Turbine Blades - Yuqiao Zheng; Rongzhen ZHAO; Hong LIU (Institute of Advanced Engineering and Science, 2014)
This paper presents a recently developed the finite model method for analysis of horizontal axis wind turbine blades. Free vibration equation is proposed based on theory of the classical lamination and Lagrange method. A 40 m rotor blade was chosen as a example study to validate the static and dynamic behaviour predicted by shell model built in ANSYS,Given uncertainty of material properties involved, an accurate agreement was found for static deformation curves, as well as a good prediction of the lowest frequency modes in terms of resonance frequencies, the highest (eighth) frequency modes show only a fair agreement as expected for an FE model, Flap-wise, edge-wise and torsional natural frequencies of a variable length blade have been investigated. The results show that the approach used in this study is very efficient and produces improved designs as compared with a reference or baseline design. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3944